2019
DOI: 10.1088/1755-1315/388/1/012069
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of white mulberry Morus alba L. fruitless cultivar using different cutting times and IBA.

Abstract: The white mulberry Morus alba L. is an interesting tree that widely planted throughout the world for various uses. The effort was made in this study to propagate the fruitless cultivar of Morus alba L. by hardwood cuttings; comparing different cuttings collection time with using various concentrations of IBA (Indole-3-Butyric Acid) solution. Results showed that taking and planting cuttings on March 1st, gave the best survival percentage of rooted seedlings, which was (20.83%) compared to February 8th (16.33%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
4
5
0
3
Order By: Relevance
“…Orgafol has a higher leaf area when compared with the other treatments. These findings are coinciding with the findings of Hawramee et al, (2019) [9] . Similar results were observed in the findings of Shah et al, (2006) [22] in Ficus binnendijkii, El-Leithy et al, (2006) [4] in Salvia officinalis, Mady (2009) [16] in faba bean, Ahmed et al,…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Orgafol has a higher leaf area when compared with the other treatments. These findings are coinciding with the findings of Hawramee et al, (2019) [9] . Similar results were observed in the findings of Shah et al, (2006) [22] in Ficus binnendijkii, El-Leithy et al, (2006) [4] in Salvia officinalis, Mady (2009) [16] in faba bean, Ahmed et al,…”
Section: Resultssupporting
confidence: 93%
“…Orgafol has the highest root length when compared with the other treatments. These findings are coinciding with the findings of Husen (2003) [10] , Intorrathed et al, (2018) [11] , Singh et al, (2014) [23] , Hawramee et al, (2019) [9] in Morus alba, Shah et al, (2006) [22] , Erturk et al, (2010) [7] , Singh (2018) [25] , Murthy et al, (2012) [18] in Matigara black and similar results were observed in the findings of Kumari et al, (2018) [15] in Morus alba, Rongting et al, (2017) [21] and Fatema et al, (2005) [8] in groundnut. The effect of the treatments on shoot length on different days after planting is shown in Table 3.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It has been proved that the natural auxin (IAA) affect most aspects of plant physiology comprising root initiation and cell division. It is generally accepted that auxins have a certain role in the rooting initiation and therefore leads to control growth and development in plants, including lateral root initiation, root gravity response and other vegetative growth parameters (Aref Hawramee et al, 2019). IAA are synthesized in buds and leaves and moved to the bottom of cuttings and grafting unions (Hartman et al 2002;Izadi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…White mulberry is a shade tolerant tree and black mulberry can tolerate atmospheric pollution which is suitable for air polluted areas (Mohiuddin et al, 2011;Kobus-Cisowska et al, 2020). Mulberry trees are commonly propagated by cutting, grafting and tissue culture (Hussain et al, 2017;Aref Hawramee et al, 2019;Zenginbal and Demir, 2018).…”
Section: Introductionmentioning
confidence: 99%